2008
DOI: 10.1080/01457630701686669
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fluid Flow and Thermal Characteristics of Plate-Fin and Pin-Fin Heat Sinks Subject to a Parallel Flow

Abstract: In this study, we compare the thermal performances of the two types of heat sinks most commonly used in the electronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…8 depicts the ratio of the thermal resistances of the optimized plate-fin and pin-fin heat sinks R opt,plate /R opt,pin as a function of dimensionless pumping power and dimensionless length. This ratio was successfully used for comparing thermal performances of plate-fin and pin-fin heat sinks with parallel-flow configuration [18]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 depicts the ratio of the thermal resistances of the optimized plate-fin and pin-fin heat sinks R opt,plate /R opt,pin as a function of dimensionless pumping power and dimensionless length. This ratio was successfully used for comparing thermal performances of plate-fin and pin-fin heat sinks with parallel-flow configuration [18]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kim et al. [11] revealed that the effective heat sink type between plate-fin and pin-fin heat sinks could be determined depending on the pumping power and heat sink length. In addition to above research activities, there has been a new attempt to combine the advantages of plate-fin and pin-fin heat sinks [12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, they studied the correlations to predict the thermal performance of crosscut heat sinks. Kim et al [33] studied the comparisons of the thermal performances of plate-fin and pin-fin heat sinks under constant pumping power conditions. Besides, they investigated the correlations to determine the thermal resistances of the optimized pin-fin heat sink.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%